2016
DOI: 10.1007/s12035-016-0294-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations in the Cerebellum of Sporadic Creutzfeldt–Jakob Disease Subtypes with DJ-1 as a Key Regulator of Oxidative Stress

Abstract: Cerebellar damage and granular and Purkinje cell loss in sporadic Creutzfeldt-Jakob disease (sCJD) highlight a critical involvement of the cerebellum during symptomatic progression of the disease. In this project, global proteomic alterations in the cerebellum of brain from the two most prevalent subtypes (MM1 and VV2) of sCJD were studied. Two-dimensional gel electrophoresis (2DE) coupled mass spectrometric identification revealed 40 proteins in MM1 and 43 proteins in VV2 subtype to be differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 103 publications
2
17
0
Order By: Relevance
“…Both the MM1 and VV2 subtypes of sCJD had significantly increased the expression of phosphorylated NRF2 in comparison to the age-matched control brains. Additionally, this increase was also observed at the protein level in both the subtypes of sCJD as compared to the age-matched control brains (Tahir et al, 2018 ).…”
Section: Activation Of Nrf2 In Prion Diseasesmentioning
confidence: 79%
See 2 more Smart Citations
“…Both the MM1 and VV2 subtypes of sCJD had significantly increased the expression of phosphorylated NRF2 in comparison to the age-matched control brains. Additionally, this increase was also observed at the protein level in both the subtypes of sCJD as compared to the age-matched control brains (Tahir et al, 2018 ).…”
Section: Activation Of Nrf2 In Prion Diseasesmentioning
confidence: 79%
“…In other words, we can say that nearly 40% of the normal respiratory chain complexes were lost after treatment of prion-infected N2a cells with ferric ions (Yuan et al, 2013 ). Recently, Tahir et al ( 2018 ) demonstrated that the reactive sulfur species in combination with the ROS and the reactive nitrogen species, which lead to multiple toxic insults, were observed in the brain of sCJD patients. The build-up of oxidative stress beyond the tolerable level within the cell will deregulate many cellular functions, such as the deregulation of energy-dependent metabolic pathways (Dringen et al, 2000 ), the impairment of energy-producing mitochondrial network (Gandhi and Abramov, 2012 ), the impairment of signal transduction (Apel and Hirt, 2004 ), the activation of the cell death pathways (Salganik, 2001 ), and the misfolding/aggregation of the pathogenic proteins (Bruijn et al, 1998 ; Valentine and Hart, 2003 ).…”
Section: Oxidative Stress In Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the molecular perspective, human cerebellum was less investigated; however, a number of dedicated proteomics studies, employing specific high‐performance analytical techniques, such as mono‐ and two‐dimensional gel electrophoresis, capillary electrophoresis, and mass spectrometry (MS) with either matrix assisted laser desorption/ionization (MALDI), MALDI‐imaging, or electrospray ionization (ESI) have demonstrated a correlation between the pattern of the cerebellum proteome and some of the pathologies affecting it, such as AD, neurodevelopmental and degenerative disorders, and neoplastic transformations occurring at this level…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DJ-1 expression has been reported to increase in cancer cells; this increase is important for cancer pathology (Kawate et al, 2017;Kim et al, 2005). Increased expression of DJ-1 within the brain cells has also been observed in several neurodegenerative diseases, such as Parkinson's disease, amyotrophic lateral sclerosis, Creutzfeldt-Jakob disease, Huntington's disease, and Alzheimer's disease (Choi et al, 2006;Lev et al, 2009;Saito et al, 2014;Sajjad et al, 2014;Tahir et al, 2018). Extracellular DJ-1 may affect the pathologies of cancer and neurodegenerative diseases and could also be a therapeutic target against inflammatory diseases and tissue injuries.…”
Section: Discussionmentioning
confidence: 98%